H2-rich syngas strategy to reduce NOx and CO emissions and improve stability limits under premixed swirl combustion mode - Samiran, N. A.; Ng, Jo-Han; Mohd Jaafar, Mohammad Nazri; ValeraMedina, Agustin; Tung, Chong Cheng (Elsevier, 2016)
The combustion performance of H2-rich model syngas was investigated by using a premixed swirl flame combustor. Syngas consisting mainly of H2 and CO was blended with components such as CH4 and CO2 in a mixing chamber prior to combustion at atmospheric condition. The global flame appearance and emissions performance were examined for high (H2/CO = 3) and moderate (H2/CO = 1.2) H2-rich syngases. Results showed that higher H2 fractions in the syngases produce lower NOx emissions per kWh basis across all equivalence ratios tested. CO emissions are equivalence ratio dependent and are less affected by the H2 fraction in the syngas. Increasing CO2 diluent ratios result in the decrease of NOx, particularly for moderate H2-rich syngases. In contrast, syngas without CO shows an increase of NOx with increasing CO2 for fuel-lean mixtures. Addition of CO2 increases the lean blowout limit of all syngases. Higher fraction of H2 produces lower lean blowout limits due to the characteristics of high diffusivity of hydrogen molecules and high flame speed that assist in the stabilisation of the flame under flame-lean conditions. The range of blowout limits for moderate and high H2-rich and pure hydrogen syngases under diluent ratios up to 25% were within the range of ϕ = 0.12–0.15.